The relationship between interhemispheric synchrony, morphine and microstructural development of the corpus callosum in extremely preterm infants. Issue 16 (11th August 2022) - Failla, Alberto; Filatovaite, Lauryna; Wang, Xiaowan; Vanhatalo, Sampsa; Dudink, Jeroen; de Vries, Linda S.; Benders, Manon; Stevenson, Nathan; Tataranno, Maria Luisa
Abstract: The primary aim of this study is to examine whether bursting interhemispheric synchrony (bIHS) in the first week of life of infants born extremely preterm, is associated with microstructural development of the corpus callosum (CC) on term equivalent age magnetic resonance imaging scans. The secondary aim is to address the effects of analgesics such as morphine, on bIHS in extremely preterm infants. A total of 25 extremely preterm infants (gestational age [GA] < 28 weeks) were monitored with the continuous two‐channel EEG during the first 72 h and after 1 week from birth. bIHS was analyzed using the activation synchrony index (ASI) algorithm. Microstructural development of the CC was assessed at ~ 30 and ~ 40 weeks of postmenstrual age (PMA) using fractional anisotropy (FA) measurements. Multivariable regression analyses were used to assess the primary and secondary aim. Analyses were adjusted for important clinical confounders: morphine, birth weight z ‐score, and white matter injury score. Due to the reduced sample size, only the most relevant variables, according to literature, were included. ASI was not significantly associated with FA of the CC at 30 weeks PMA and at 40 weeks PMA ( p  > .5). ASI was positively associated with the administration of morphine ( p  < .05). Early cortical synchrony may be affected by morphine and is not associated with the microstructural development of the CC. More studies are needed to evaluate the long‐term effects of neonatal morphine treatment to optimize sedation in this high‐risk population. Abstract : The absence of relationship between activation synchrony index (ASI) and fractional anisotropy of corpus callosum before term equivalent age. ASI is positively influenced by morphine dosage.